Scale of Coping with Pain for Dancers (COPAIN-Dancer): Construction and validity evidences - Becker da Silva, Andressa Melina (2018)
Dancers experience daily pain that impacts their health, but the pain is mediated by coping with pain. We elaborated the Scale of Coping with Pain for Dancers (COPAIN-Dancer) based on the Motivational Theory of Coping with 12 categories of coping. This study presents the validity of the COPAIN-Dancer. The content analysis conducted judges reduced 118 items to 35, that were then administered to 386 Brazilian dancers between 10 and 19 years old (M=15.35; SD=3.36). Applying the Exploratory Factor Analysis, a low correlation resulted among the items that represent the 12 coping categories. However, after conducting Item Response Theory and Network Analysis, we obtained two factors: Adaptive Coping and Maladaptive Coping. The COPAIN-DANCER shows reliability and can be used in adolescent dancers.